Technologies and Conditions for Participation and Empowerment of Rural Communities in Restoring Degraded Sites in Mabira Forest Reserve, Central Uganda - Eilu, G.; Galabuzi, C.; Mulugo, L.; Kakudidi, E.; Tabuti, J.R.S.; Sibelet, N. (World Agroforestry Congress, 2009)
Forests and related tree based resources contribute to > 90% of the livelihoods of neibouring communities (FAO 1981) These resources are often degraded because the user local people are not empowered to rehabilitate them. The technologies to employ and conditions for local participation are often not clear. This study was conducted to i) identify the technologies that can be locally promoted to restore degraded forest sites; and ii) determine the conditions for empowering the local people to participate in forest restoration.